RECURRENT HERPES SIMPLEX: EVALUATION OF INTERFERONOGENESIS AT THE LOCAL AND SYSTEMIC LEVELS - Horbal, N.M.; Potemkina, G.O.; Kril, I.J.; Gaiduchok, I.G.; Fedorov, Y.V.; Chopyak, V.V. (World of Medicine and Biology, 2021)
In this article, the authors propose the results of the investigation of the interferon–alpha synthesis dynamics at the local and systemic levels in patients with recurrent herpes simplex virus, analyzed the effect of different types of therapy on the interferon–alpha synthesis and established the clinical efficacy depending on the therapy received. It was found that patients with mild herpes simplex after antiviral therapy and during follow–up showed normalization of the interferon–alpha level. The results indicate the stabilization of antiviral protection in patients who received antiviral therapy (acyclovir and/or inosine pranobex) and the possible further persistence of the virus in patients treated by acyclovir and/or placebo. The clinical efficacy of antiviral treatment of patients with recurrent herpes simplex virus was established: with a mild course of infection after treatment it was 73.5 %, during follow–up – 85.8 %; with a medium to severe and a severe – after treatment – 64.0 %, during follow–up – 70.4 %.